Regional ionospheric mapping and modelling over Antarctica - B. Zolesi; G. De Franceschi (Annals of Geophysics, 1998)
The performance of regional and global models has been investigated when applied for long term mapping of ionospheric characteristics and modelling the Total Electron Content in the polar cap over an Antarctic region. Comparison results between modelled data and a short period of experimental values available for low solar activity in December 1993 and January 1994 are presented and discussed.